Perburuan Satwa di Papua (Short Reviewer) - Pattiselanno, Freddy (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2006)
Many people in West Papua value forest for the benefits obtained from the extraction of plants and animals. Hunting and gathering of wild animals has always been and continues to be an important aspect of life in rural West Papuan communities. Even in modern days, some ethnic groups in West Papua depend almost entirely on hunting as a part of their tradition (Pattiselanno, 2003). In other words, hunting is one of the main ways of living.